2020
DOI: 10.1111/nmo.13876
|View full text |Cite
|
Sign up to set email alerts
|

Ineffective esophageal motility and bolus clearance. A study with combined high‐resolution manometry and impedance in asymptomatic controls and patients

Abstract: Background The definition and relevance of ineffective esophageal motility (IEM) remains debated. Our aim was to determine motility patterns and symptoms associated with IEM defined as impaired bolus clearance. Methods To define altered bolus clearance, normal range of swallows with complete bolus transit (CBT) on high‐resolution impedance manometry (HRIM) was determined in 44 asymptomatic controls. The results were then applied to a cohort of 81 patients with esophageal symptoms to determine the motility patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 25 publications
2
27
1
3
Order By: Relevance
“…Fragmented peristalsis is now removed as a disorder and incorporated into the overall diagnosis of IEM (Very Low GRADE, Strong Recommendation). 60,61 Disorders of peristalsis are considered when a disorder of EGJ outflow has been ruled out. There is potential for overlapping features of abnormal peristalsis to exist.…”
Section: Disorder S Of Peris Tal S Is ( Tab Le S 3)mentioning
confidence: 99%
See 2 more Smart Citations
“…Fragmented peristalsis is now removed as a disorder and incorporated into the overall diagnosis of IEM (Very Low GRADE, Strong Recommendation). 60,61 Disorders of peristalsis are considered when a disorder of EGJ outflow has been ruled out. There is potential for overlapping features of abnormal peristalsis to exist.…”
Section: Disorder S Of Peris Tal S Is ( Tab Le S 3)mentioning
confidence: 99%
“…Consistent with prior iterations of Chicago Classification, absent contractility, DES, hypercontractile esophagus, and IEM are considered disorders of peristalsis. Fragmented peristalsis is now removed as a disorder and incorporated into the overall diagnosis of IEM (Very Low GRADE, Strong Recommendation) 60,61 . Disorders of peristalsis are considered when a disorder of EGJ outflow has been ruled out.…”
Section: Disorders Of Peristalsis (Table S3)mentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of high‐resolution manometry (HRM) and esophageal pressure topography (EPT), these criteria were translated as distal contractile integral (DCI) < 450 mm Hg.cm.s to define ineffective swallows, and ≥50% ineffective swallows are required for an IEM diagnosis according to the Chicago Classification 3.0 6 . Studies have found that IEM can impair esophageal clearance and might be an important contributing pathophysiologic factor in GERD 3,4,7–9 …”
Section: Introductionmentioning
confidence: 99%
“…6 Studies have found that IEM can impair esophageal clearance and might be an important contributing pathophysiologic factor in GERD. 3,4,[7][8][9] Secondary peristalsis contributes to maintenance of an empty esophagus by clearing refluxed gastric contents or residual food bolus after a failed primary peristalsis or after a reflux event. 10 This plays an important role in the return of esophageal pH to baseline following a reflux event, in order to prevent prolonged acid exposure in the esophagus.…”
mentioning
confidence: 99%